2017
DOI: 10.2139/ssrn.3187832
|View full text |Cite
|
Sign up to set email alerts
|

Capital Flows and Financial Stability in Emerging Economies

Abstract: The views expressed in this publication are those of the authors and do not necessarily reflect the views and policies of the Asian Development Bank (ADB) or its Board of Governors or the governments they represent. ADB does not guarantee the accuracy of the data included in this publication and accepts no responsibility for any consequence of their use. The mention of specific companies or products of manufacturers does not imply that they are endorsed or recommended by ADB in preference to others of a simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Stiglitz (2000) particularly advised against short-term capital flows but opined that FDI, on the other hand, leads to increased access to market, human capital, valuable training, technology and resources. This argument is supported by Baum et al (2017), who used 16 emerging and newly industrialized countries to examine whether different flows have different significant effects on financial stability for different economies. Using seemingly unrelated regression (SUR) method developed by Zellner (1962), six measures of gross capital flows and five financial variables for measuring financial stability, findings suggest that the effects of different measures of capital flows might not be equal across all countries.…”
Section: Brief Literature Reviewmentioning
confidence: 96%
See 3 more Smart Citations
“…Stiglitz (2000) particularly advised against short-term capital flows but opined that FDI, on the other hand, leads to increased access to market, human capital, valuable training, technology and resources. This argument is supported by Baum et al (2017), who used 16 emerging and newly industrialized countries to examine whether different flows have different significant effects on financial stability for different economies. Using seemingly unrelated regression (SUR) method developed by Zellner (1962), six measures of gross capital flows and five financial variables for measuring financial stability, findings suggest that the effects of different measures of capital flows might not be equal across all countries.…”
Section: Brief Literature Reviewmentioning
confidence: 96%
“…While Dhal et al (2011) argue that financial stability, growth and inflation could share a medium- to long-term relationship and enhance financial stability associated with higher growth accompanied by stable interest rate. Baum et al (2017) found that after controlling for macroeconomic factors, the effect of capital flows on financial stability varies quite substantially across countries and interestingly across the various types of flows. In light of the above, this study, therefore, adopts inflation rate and GDP growth rate as control variables.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is worth paying attention to Keliuotytė-Staniulėnienė (2015), Perciun et al (2014), and Semjonova (2016). Baum et al (2017) analyze financial security in the system of economic security of the state by study-ing the problems of capital flows and financial stability. Korauš et al (2016) address the problem of ensuring the banking component of the country's financial security.…”
Section: Literature Reviewmentioning
confidence: 99%